Pengaruh Keputusan Pendanaan dan Intellectual Capital Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening pada Perusahaan Sektor Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia - Hrp, Nadra Angraini; Syahyunan, Syahyunan; Aditi, Bunga (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to investigate and analyze the influence of financing decisions and intellectual capital on company value with profitability as an intervening variable in the food & beverage sector companies listed on the Indonesia Stock Exchange. The study applied specific criteria for sample selection, utilizing purposive sampling technique, resulting in a total of 11 companies with 55 data points. The researcher employed path analysis and panel data regression to address the research hypotheses. The results of this study indicate that financing decisions have a positive contribution to profitability. Intellectual capital positively influences profitability. Financing decisions significantly affect company value, and intellectual capital also affects company value. Profitability directly influences company value. Additionally, financing decisions affect company value through profitability, and intellectual capital affects company value through profitability as well